2018
DOI: 10.1111/1759-7714.12793
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between progression‐free survival, tumor burden, and circulating tumor DNA in the initial diagnosis of advanced‐stage EGFR‐mutated non‐small cell lung cancer

Abstract: BackgroundThis study was conducted to identify whether the presence of circulating tumor DNA (ctDNA) in plasma before treatment with EGFR‐tyrosine kinase inhibitors (TKIs) is associated with clinical outcomes.MethodsFifty‐seven pairs of tissues and plasma samples were obtained from patients with NSCLC adenocarcinoma harboring activating EGFR mutations before the administration of EGFR‐TKI treatment. ctDNA mutation was identified using the PANAMutyper EGFR mutation kit. Both qualitative and quantitative analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Univariate analyses of our results showed a negative correlation between a detectable baseline plasma EGFR ctDNA and PFS. This result is consistent with some reports performed in metastatic NSCLC patients [21][22][23][24][25]. Given that ctDNA values are correlated with tumour burden, we speculate that these patients with radiological local disease but detectable baseline plasma EGFR ctDNA may harbour a higher systemic burden and do poorly despite local radical treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Univariate analyses of our results showed a negative correlation between a detectable baseline plasma EGFR ctDNA and PFS. This result is consistent with some reports performed in metastatic NSCLC patients [21][22][23][24][25]. Given that ctDNA values are correlated with tumour burden, we speculate that these patients with radiological local disease but detectable baseline plasma EGFR ctDNA may harbour a higher systemic burden and do poorly despite local radical treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In advanced NSCLC, ctDNA detection is related to tumor burden as well as extrathoracic lymph node and bone metastasis [24]. In early-stage NSCLC, Abbosh et al showed that nonadenocarcinoma histology, lymphovascular invasion, and high Ki-67 proliferation index were…”
Section: Plos Onementioning
confidence: 99%
“…Currently, a number of studies have shown that a high concentration of cfDNA at baseline represents a negative prognostic factor in terms of PFS and OS, irrespectively of patient characteristics like age and smoking habits, treatments and tumor histological type [13,[30][31][32][33]. In this regard, Cargnin et al performed a systematic review and meta-analysis to evaluate the impact of baseline cfDNA levels on the progression and survival of lung cancer patients.…”
Section: Circulating Cell-free Dnamentioning
confidence: 99%